Weekly Variations of Intracerebral Hemorrhage Occurrence Among Different Populations: A Cross-Sectional Study - Yun-Tao Pu; Ning Yan; En-Yuan Wang; Yan-Yue Wang (Frontiers in Neurology, 2021)
Background and purpose: The causes of the higher incidence of intracerebral hemorrhage (ICH) on a given day are unclear. Previous studies have shown that it may vary by region and population. The purpose of this study was to detect weekly variations in ICH occurrence in southwest China and to assess differences in ICH occurrence among different populations.Methods: This hospital-based study included patients with first-onset ICH that occurred from January 1, 2012, to December 31, 2019. The weekly variation in ICH occurrence was analyzed and stratified by sex, age, comorbidities, living habits, and residence.Results: A total of 5,038 patients with first-onset ICH were enrolled. ICH occurrence was higher on Monday [odds ratio (OR), 1.22; 95% CI, 1.09–1.36; P < 0.001] and Friday (OR, 1.15; 95% CI, 1.03–1.28; P < 0.001) among all patients, and this pattern was consistent with that of men, whereas women showed a higher incidence on Mondays, Saturdays, and Sundays. The increase in the number of ICH events on Monday and Friday was pronounced in the age range of 41–60 years; however, no significant weekly variation in ICH occurrence was observed among other age groups. After stratifying by comorbidities, a significant weekly variation in ICH occurrence was observed in patients with hypertension or diabetes. Smoking and alcohol consumption was associated with a higher incidence of ICH on Friday; otherwise, a Monday excess was observed. The urban population demonstrated a significant weekly variation in ICH occurrence, whereas the rural population did not.Conclusions: Intracerebral hemorrhage occurrence showed weekly variations in southwest China and was significantly affected by sex, age, comorbidities, living habits, and residence. This suggests that weekly variations in ICH occurrence maybe dependent on the region and population.